E-wallet utilization via QR code: an empirical study on relevant predictors among M40 millennials in Malaysia - Lim, Foo Wah (2019)
The Malaysian government is pushing for a cashless society but going cashless is all the rage now. The adoption of e-wallet in Malaysia is still in the infancy stage, and the reasons to explain the behavioural intention to use e-wallet transaction via QR code are remaining unclear. To address these requisites, the purpose of this study is to examine the predictors of the behavioural intention to use e-wallet transaction via QR code among M40 millennials in Malaysia. An integrative theoretical framework was developed based on the perspectives of the Technology Readiness Index (TRI) and the Unified Theory of Acceptance and Use Technology model (UTAUT). To test the framework, the quantitative approach using the survey method was used. By using a self-administered survey, the data were obtained from 487 respondents from the M40 millennials in Malaysia. The data were then analysed utilising the Partial Least Square Structural Equation Modelling (PLS-SEM) technique. The finding showed that of all the four TRI elements, only optimism and innovativeness are relevant to behavioural intention to use e-wallet transaction via QR code in Malaysia nowadays. Besides, the findings indicate that performance expectancy and effort expectancy in UTAUT have significant positive influences on the behavioural intention to use e-wallet transaction via QR code among M40 millennials in Malaysia. More importantly, the findings indicated that overall optimism has positive, statistically significant effects on behavioural intention, through the full mediating effect of performance expectancy and effort expectancy. Additionally, innovativeness through the mediating effect of performance expectancy and effort expectancy indicated a partial mediating effect. The results of this study will contribute in terms of theoretical, managerial and methodological perspectives. It will use to contribute to the financial institutions in Malaysia significantly. Nonetheless, further studies are necessary both to confirm the findings and to incorporate additional variables that may influence results. Lastly, limitations and recommendation for future studies are presented.